Observational Instruments in the Arab Scientific Heritage Perspective Ismail ibn Heba Allah al-Hamawi | Al Alät Al Rosydiyyah fi At Thurost Al ‘Ilm Al ‘Aroby ‘Indä Ismäil ibn Hebä Allah al-Hämäwi - Elkhayati Rifai (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The article is an edited and critical study of an unpublished astronomical text entitled